A Systematic Review of the Potential of Pichia pastoris (Komagataella phaffii) as an Alternative Host for Biologics Production - Vijayakumar, Vijay Elakkya; Venkataraman, Krishnan (Molecular biotechnology, 2024)
The methylotrophic yeast Pichia pastoris is garnering interest as a chassis cell factory for the manufacture of recombinant proteins because it effectively satisfies the requirements of both laboratory and industrial set up. The optimisation of P. pastoris cultivation is still necessary due to strain- and product-specific problems such as promoter strength, methanol utilisation type, and culturing conditions to realize the high yields of heterologous protein(s) of interest. Techniques integrating genetic and process engineering have been used to overcome these problems. Insight into the Pichia as an expression system utilizing MUT pathway and the development of methanol free systems are highlighted in this systematic review. Recent developments in the improved production of proteins in P. pastoris by (i) diverse genetic engineering such as codon optimization and gene dosage; (ii) cultivating tactics including co-expression of chaperones; (iii) advances in the use of the 2A peptide system, and (iv) CRISPR/Cas technologies are widely discussed. We believe that by combining these strategies, P. pastoris will become a formidable platform for the production of high value therapeutic proteins. Graphical Abstract